THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE SYSTEM OF PROFESSIONAL DEVELOPMENT OF TEACHERS (Archive of Conferences, 2020)
Due to the widespread introduction of advanced computer technology, the activities of any institution today cannot be imagined without the direct participation of information and communication technology. This creates a need for professionals who are well versed in the use of ICT tools and programs for these institutions.